HARMONY OF STAGE AND HEART: ARTISTIC ANALYSIS OF MAKSET ESIMBETOV’S WORK - JANABAEV , MIYIRBEK; BAKHIEVA , BIYBINAZ (INTERNATIONAL CONFERENCE ON SCIENCE, INNOVATION AND GLOBAL DEVELOPMENT, 2026)
This article provides a comprehensive overview of the life and creative work of Maksset Esimbetov, a prominent representative of Karakalpak theatrical art and an Honored Artist of Karakalpakstan.